1987
DOI: 10.1111/j.1365-2125.1987.tb03208.x
|View full text |Cite
|
Sign up to set email alerts
|

Lack of correlation between methotrexate concentrations in serum, saliva and sweat after 24 h methotrexate infusions.

Abstract: 1 Methotrexate (MTX) concentrations were studied in serum, mixed saliva and sweat during and after 24 h continuous MTX infusions (0.5‐6 g m‐2) in 14 patients with various malignant diseases. 2 The serum‐MTX concentrations declined in a biphasic manner, but the MTX elimination in saliva and sweat varied to a much greater extent. 3 Saliva/serum and sweat/serum ratios during the MTX infusion were 2.3% and 0.55% respectively. The ratios had increased significantly 20 and 44 h postinfusion. 4 No correlations were d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0
2

Year Published

1989
1989
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 13 publications
0
6
0
2
Order By: Relevance
“…Several investigators have reported an even lower ratio of 1 to 2.3% between measured salivary and serum concentrations of MTX in patients who received HD-MTX [5,8]. Although only 50 to 70% of MTX in serum is bound to protein and the remaining 30 to 5070, as free MTX, might be expected to contribute to the salivary MTX concentration, the low observed salivary MTX levels might be attributable to either a physiological barrier against MTX influx into saliva or its rapid removal from saliva [ 5 ] .…”
Section: Discuss I 0 Nmentioning
confidence: 98%
“…Several investigators have reported an even lower ratio of 1 to 2.3% between measured salivary and serum concentrations of MTX in patients who received HD-MTX [5,8]. Although only 50 to 70% of MTX in serum is bound to protein and the remaining 30 to 5070, as free MTX, might be expected to contribute to the salivary MTX concentration, the low observed salivary MTX levels might be attributable to either a physiological barrier against MTX influx into saliva or its rapid removal from saliva [ 5 ] .…”
Section: Discuss I 0 Nmentioning
confidence: 98%
“…This was achieved by the use of human tumour cell lines covering the spectrum of MTX-sensitive tumours (Jolivet et al, 1983), by selection of a 24 h MTX exposure period and by using MTX and FA concentrations representative of the clinical context (Stoller et al, 1977;Straw et al, 1984;Parker et al, 1986;Milano et al, 1986;Schroder et al, 1987;Borsi & Moe, 1987;Schilsky et al, 1989). Among the clinically relevant conclusions which can be drawn from the present study, the optimum time interval between MTX and FA appears to be around 18-24 h; a marked reduction in MTX cytotoxicity occurs during shorter intervals.…”
Section: Discussionmentioning
confidence: 99%
“…A small amount of MTX is excreted into saliva and sweat. Schrøder et al [133] reported the variation of the MTX excretion into saliva and sweat after 24 h continuous MTX infusion (0.5–6 g/m 2 ) in 14 patients with various malignant diseases. In the study, there were two patients, whose renal MTX excretions were markedly delayed, and in one of them, the salivary MTX elimination was also retarded.…”
Section: Introduction For Methotrexatementioning
confidence: 99%